Gamification-Based Adaptive Physical Education Model for Gross Motor Skills in Students with Intellectual Disabilities - Septaliza, Dewi; Endrawan, I Bagus; Nugroho, Dwi Susilo; Aliriad, Hilmy; Isnaini, Lalu Moh Yudha (Indonesian Journal of Physical Education and Sport Science, 2026)
Study purpose. Adaptive physical education for students with intellectual disabilities faces persistent challenges including low motivation, limited attention span, and suboptimal gross motor skill development. This study aimed to develop, validate, and analyze the effectiveness of a gamification-based adaptive physical education learning model for improving gross motor skills in students with intellectual disabilities. Materials and methods. A Research and Development (R&D) approach was employed, comprising needs analysis, product design, development, small-group trials (n = 15), large-group trials (n = 60), and a product effectiveness test (n = 60) using a one-group pretest–posttest design. Instruments included expert validation sheets, observation sheets, response questionnaires, and an adaptive gross motor test. Data were analyzed using SPSS version 29. Results. Results showed the model was highly valid (mean score 90.2%), achieved very good implementation rates (86.7% and 88.4%), and significantly improved students’ gross motor skills, t(59) = 14.87, p < 0.001, with a very large effect size (Cohen’s d = 1.95). Conclusions. The gamification-based adaptive physical education learning model is valid, practical, and effective for students with intellectual disabilities. Future research should employ stronger experimental designs with control groups and longer intervention durations.